Invasive Bladder Cancer - Bassi, PierFrancesco; Pagano, Francesco (Springer London : Imprint: Springer, 2007)
Invasive Bladder Cancer draws on the expertise of an international community of experts in the area. It offers an updated, simple overview bridging the information coming from basic research to clinical practice, facilitated by most chapters having both a basic researcher and a clinician writing together. The book will be of particular interest to office urologists, and oncologists with a specialist interest in urology.